Multigenerational modelling incorporating time lag in innovation adoption. (26th August 2021) - Singh, Ompal; Singhal, Shakshi; Anand, Adarsh
The present study seeks to analyse the adoption process of multigenerational innovation using a stage structure. Innovation diffusion modelling has gained notable attention from researchers over many decades. In this paper, a novel diffusion model is proposed that analyses the substitution phenomenon among simultaneous generations by explicitly considering a time delay between the product awareness and adoption phase. A random time delay function following an Erlang distribution is incorporated to analyse the factual adoption process. The paper provides new insights gleaned by implementing the proposed framework on actual sales data of LCD computer monitors. Findings demonstrate that the new diffusion models exhibit better prediction capability among all the studied models. Besides, the developed model can find application in various industries as it is computationally viable and flexible.